Solitary round pulmonary lesions in the pediatric population: a pictorial review. (May 2019) - Arkoudis, Nikolaos-Achilleas; Pastroma, Angeliki; Velonakis, Georgios; Tsochatzis, Athanasios; Mazioti, Argyro; Vakaki, Marina; Alexopoulou, Efthymia
The purpose of this current pictorial review is to define the solitary round pulmonary lesion (SRPL), to familiarize with its prevalence in the pediatric population, and, moreover, to educate radiologists on its vast differential diagnosis and imaging manifestations. Furthermore, by highlighting valuable clues, it intends to assist radiologists efficiently partake in its diagnosis, work-up, and follow-up in order to narrow down the differential diagnosis by working alongside the clinician and combining clinical information, lab results, and radiological findings.